Computational thinking: Enhancing STEAM and engineering education, from theory to practice. Issue 1 (6th January 2021) - Dolgopolovas, Vladimiras; Dagienė, Valentina
Abstract: This publication provides an editorial introduction to a special issue of Computer Applications in Engineering Education journal entitled Computational Thinking for STEM and Engineering Education. It provides introductory remarks to the issue and a commentary on the published material, as well as presents the views of the special issue editors in the field of science, technology, engineering and mathematics (STEM) education and research. This special issue is structured as follows. It contains articles related to the topics of computational thinking (CT), STEM, and engineering education. It starts with three overview articles based on systematic reviews, giving a structured overview of CT concepts in terms of practical educational approaches in introductory science, technology, engineering, arts and mathematics (STEAM) education. Subsequent articles present practical approaches to CT and STEAM education in such educational areas as general engineering, programming and software engineering, physical computing, robotics, electronics, mechanical, and power engineering.